Nutri fine herbs bread roll – bitter and Better for diabetics - S. VIJAYALAKSHMI; T. KANCHANA; A. ARUN; K. MANIVEL (International Journal of Pharma and Bio Sciences, 2016)
Diabetes is expected to become the world’s largest killer by 2030. Nutrition supplement plays an important role for people with diabetes. Mounting evidences of chemical and pharmacological research work, numerous bioactive compounds have been found in functional herbal food ingredients for diabetes. As a result there is a rapidly increasing interest in developing new food formulas which enhance health of diabetics. The aim of the present study is to prepare two different bread rolls with the incorporation of Aloe vera (Product A) and Cissus quadrangularis (Product B) and to experiment for its acceptance level of the consumers by sensory evaluation method using 9 point hedonic rating scale in the food science laboratory and to calculate the nutritive value of each bread roll using Nutritive value of Indian foods by NIN. The mean sensory score of acceptance test was found lower due to the increased intensity of bitter taste of Product A than Product B. The results conclude that functional and health products with improved sensory quality could be developed by adding Aloe vera and Cissus quadrangularis to many other bakery products.